(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The current study aimed to describe some of the variables related to the contingencies established by the Bolsa Família Program (BFP) and to analyze the effect of the establishment of rules/laws on the behavior of “going to school” of children, adolescents and youth based on principles of Behavior Analysis. For this, a review of the concept of rules and on the characteristics of the PBF was made. The Government, as a controlling agency, makes use of laws that aim to determine the behavior of the citizens: BFP is a strategy of the Brazilian government to extinguish the behavior of the population, such as not attending school among others. It was concluded that the behavior of “going to school” can become insensitive to contingencies when people follow the rule regardless of the natural consequences of this behavior, and that motivational variables should be carefully analyzed and managed.